To factorise cubic polynomial p(x), we

- Find x = a where p(a) = 0
- Then (x – a) is the factor of p(x)
- Now divide p(x) by (x – a) i.e. (p(x))/((x - a))
- And then we factorise the quotient by splitting the middle term

Let us take an example

In Example 15 ,

- We first find x where p(x) = 0.
- x = 1
- So, (x – 1) is a factor of p(x)
- We divide p(x) by (x – 1)
- We get quotient g(x)
- We factorise g(x) using splitting the middle term

Learn in your speed, with individual attention - Teachoo Maths 1-on-1 Class